Cumulative stress: A general "s" factor in the structure of stress. (November 2021) - Mann, Frank D.; Cuevas, Adolfo G.; Krueger, Robert F.
Abstract: Objective: The present study tested a hierarchical model of cumulative stress in a large probability sample of adults from the United States. Methods: Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) models were used to develop and test a hierarchical model of cumulative stress. Structural equation models were used to estimate concurrent associations with demographic factors, polygenic risk scores, and physical health outcomes, as well as prospective associations with physical health outcomes. Results: A hierarchical model of cumulative stress was the best-fitting model, with a general "s-factor" capturing the tendency for subordinate dimensions of stress to correlate. Associations with demographic factors and polygenic risk scores for physical and psychological phenotypes provide evidence for the convergent validity of a general s-factor of cumulative stress. The general s-factor and subordinate factors of cumulative stress were also associated with physical health outcomes, concurrently and prospectively, including number of chronic conditions, body mass index, and difficulty with activities of daily living. Conclusions: Like other human individual differences, the co-occurrence of social stressors can be understood using a hierarchical model. Highlights: The current study provides evidence for a hierarchical model of cumulative stress. Demographic and cohort differences provide evidence for convergent validity. Prospective links with health outcomes provide evidence for predictive validity. Social stressors can be understood using a hierarchical model.